Anticholinergic drugs and risk of dementia: case-control study. (25th April 2018) - Richardson, Kathryn; Fox, Chris; Maidment, Ian; Steel, Nicholas; Loke, Yoon K; Arthur, Antony; Myint, Phyo K; Grossi, Carlota M; Mattishent, Katharina; Bennett, Kathleen; Campbell, Noll L; Boustani, Malaz; et al.
Abstract: Objectives: To estimate the association between the duration and level of exposure to different classes of anticholinergic drugs and subsequent incident dementia. Design: Case-control study. Setting: General practices in the UK contributing to the Clinical Practice Research Datalink. Participants: 40 770 patients aged 65-99 with a diagnosis of dementia between April 2006 and July 2015, and 283 933 controls without dementia. Interventions: Daily defined doses of anticholinergic drugs coded using the Anticholinergic Cognitive Burden (ACB) scale, in total and grouped by subclass, prescribed 4-20 years before a diagnosis of dementia. Main outcome measures: Odds ratios for incident dementia, adjusted for a range of demographic and health related covariates. Results: 14 453 (35%) cases and 86 403 (30%) controls were prescribed at least one anticholinergic drug with an ACB score of 3 (definite anticholinergic activity) during the exposure period. The adjusted odds ratio for any anticholinergic drug with an ACB score of 3 was 1.11 (95% confidence interval 1.08 to 1.14). Dementia was associated with an increasing average ACB score. When considered by drug class, gastrointestinal drugs with an ACB score of 3 were not distinctively linked to dementia. The risk of dementia increased with greater exposure for antidepressant, urological, and antiparkinson drugs with an ACB score of 3. This result was also observed for exposure 15-20 years before a diagnosis. Conclusions: A robust association between some classes of anticholinergic drugs and future dementia incidence was observed. This could be caused by a class specific effect, or by drugs being used for very early symptoms of dementia. Future research should examine anticholinergic drug classes as opposed to anticholinergic effects intrinsically or summing scales for anticholinergic exposure. Trial registration: Registered to the European Union electronic Register of Post-Authorisation Studies EUPAS8705.